Derivatives usage in non-financial firms - Mohamad, Mohamad Hanapi; Mohd Faizal, Mohd Amin (Penerbit Universiti Utara Malaysia, 2005)
Derivatives are commonly used by financial firms in order to protect themselves from unforeseen losses due to currency fluctuations.The degree of usage should demonstrate the equivalent level of risk the firms intend to cover, hence the bigger the foreign exchange exposure, the bigger the coverage.This study attempted to describe derivative usage in non-financial firms.Cross section data from developed and developing countries were used to assess the degree of usage the degree of usage.The findings revealed that while in developed countries the usages are very rigorous, derivatives are also becoming popular in developing countries.The reason for the usage also indicated similarity between developed and developing countries.